Alterations in angina threshold with nifedipine during pacing induced angina. Issue 3 (September 1984) - Kramer, P H; Chatterjee, K; Schwartz, A; Swedberg, K; Rouleau, J L; Curran, D; Blevins, L; Parmley, W W
Abstract : Changes in coronary haemodynamics and angina threshold were determined during atrial pacing in 11 patients with fixed obstructive coronary artery disease with effort angina before and after the administration of 20 mg of oral nifedipine. Coronary vascular resistance decreased at resting and at "subangina" heart rates but not at "angina" rates. Primary coronary vasodilatation with nifedipine was also suggested by higher coronary sinus oxygen content whether at rest or at subangina or angina heart rates. After nifedipine angina occurred at a lower double product and lower myocardial oxygen consumption. These findings suggest that nifedipine is a coronary vasodilator, but angina can occur at a lower angina threshold in some patients with obstructive coronary artery disease.